Pressureless sintering of Ceria [Resumo] - Silva, P. Oliveira e (2020)
ABSTRACT: Cerium oxide (CeO2), known as ceria, is widely used in several applications, such as automobile exhaust catalysts, electrolytes in solid oxide fuel cells, electrodes in gas sensors, and ultraviolet absorbents, owing to superior thermal and chemical stability, high ionic conductivity, good oxygen storage or release capacity and strong UV absorption.